Prognostic nutritional index predicts survival in intermediate and advanced hepatocellular carcinoma treated with hepatic arterial infusion chemotherapy combined with PD-(L)1 inhibitors and molecular targeted therapies - Hao-Huan Tang; Ming-Qing Zhang; Zi-Chen Zhang; Chen Fan; Shu-Shu Li; Wei Chen; Wei-Dong Wang (BMC Cancer)
Abstract Background This study aimed to evaluate the predictive efficacy of the prognostic nutritional index (PNI) in patients with intermediate and advanced hepatocellular carcinoma (HCC) treated with a regimen consisting of hepatic arterial infusion chemotherapy (HAIC), PD-(L)1 inhibitors, and molecular targeted therapies (MTTs). Methods A retrospective analysis was performed on the data of 88 HCC patients received triple therapy between January 2020 and August 2022 at three medical centers. Univariate and multivariable analyses were conducted to assess the relationship between PNI and survival outcomes. Results The median follow-up was 11.0 months (IQR: 8.0–17.0). The PNI cut-off value of 38.6 was determined using receiver operating characteristics (ROC) analysis. The median overall survival (OS) durations were 29.0 and 8.0 months in the high-PNI (≥ 38.6) and low-PNI (≤ 38.6) groups, respectively (HR = 0.306, 95% CI, 0.170–0.552, P < 0.001), and the median progression-free survival (PFS) durations were16.0 and 6.0 months, respectively (HR = 0.521, 95% CI, 0.303–0.896, P = 0.014). A higher complete response rate was observed in the high-PNI group (17.5% vs. 3.2%, P = 0.033). The univariate and multivariable analyses revealed that a PNI of ≥ 38.6 had an independent influence on both median OS (HR = 0.296; 95% CI, 0.159–0.551, P < 0.001) and median PFS (HR = 0.560; 95% CI, 0.318–0.987, P = 0.045). Conclusion The PNI is an objective and convenient tool that can potentially predict the prognosis of patients treated with HAIC-based triple therapy.